An Assessment of The Relevance of Immanuel Kant’s Conception of Moral Ethics as a Solution to Corrupt Practices in Nigerian Politics - Orji, Chidi Paul; Egberongbe, Tijani Taiwo; Nwagbara, Rufus Godswill; Chukwu, Peter Damian Ezechi (NIU Journal of Humanities; Vol 10 No 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025DO - 10.58709/niujhu.v10i1.2100, 2025)
The prevalence of corruption in Nigerian society is not only a hunch; rather, it has become a national disgrace. It is a significant obstacle to both sustainable growth and the democratization of Nigeria's political landscape. There have been several attempts throughout this country's history to stop the spread of this monster. Immanuel Kant's ethics' postulation and prescription on the impact of corruption on national development were the focus of the study, which used conceptual, critical, and analytical methods. According to Kant, there is a close relationship between categorical imperatives and morality; morality must be founded on the categorical imperative as it is imperative and cannot be disregarded or claimed to be irrelevant. The conclusion drawn by the article is that, given the lack of progress in Nigeria's numerous attempts to combat corruption, Nigerians must alter their behavior if the country is to experience lasting and sustainable development. Kant's Categorical Imperatives, which states that one should always act and behave as though one's course of action or line of conduct were a universal or general law, is a necessary tool for doing so. K e ywords: Kant, Categorical Imperatives, Corruption, Nigeria